Developing a nursing diagnosis for the risk for malnutrition: a mixed‐method study - Silvia Brunner; Hanna Mayer; Matthias Breidert; Michael Dietrich; Maria Müller‐Staub (Wiley, 2021)
Abstract Aim As the risk for malnutrition in older people in hospitals is often underreported, we aimed to develop a risk nursing diagnosis, including label, definition and risk factors. Design A convergent parallel mixed‐methods design was employed. Methods A literature review led to risk factors, validated by 22 hospitalized older people's perspectives and observations, including their nursing records. Per participant, one interview (qualitative), one non‐participatory observation of three meals (198 hr; qualitative) and one nursing record evaluation (quantitative) were conducted. Findings According to the classification system of NANDA International, the risk for protein-energy malnutrition is defined with 18 risk factors, including associated conditions. Content validated risk factors are presented from three participants with the most, medium and least coherent nursing record, measured with the Quality of Diagnosis, Intervention and Outcomes tool. Conclusion This new nursing diagnosis supports nurses to manage the risk for malnutrition and optimize older people's nutrition.